2009
DOI: 10.1175/2009jcli2973.1
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variations of the East Asian Winter Monsoon and Their Association with Quasi-Stationary Planetary Wave Activity

Abstract: Interdecadal variations of the East Asian winter monsoon (EAWM) and their association with the quasistationary planetary wave activity are analyzed by using the 40-yr European Centre for Medium-Range Weather Forecasts Re-Analysis dataset and the National Centers for Environmental Prediction-National Center for Atmospheric Research reanalysis dataset. It is found that the EAWM experienced a significant weakening around the late 1980s; that is, the EAWM was strong during 1976-87 and became weak after 1988. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 31 publications
(38 reference statements)
8
110
0
5
Order By: Relevance
“…Climatologically last days of CDD appeared in later half of winter monsoon (see Supplement-2). Recently, Wang et al (2009) found that the East Asian winter monsoon became weaker since around the late 1980s. The weakening of the East Asian winter monsoon suggests a decrease of frequency and/or intensity of the cold surge from Siberia into the South China Sea and the Philippine Sea.…”
Section: Resultsmentioning
confidence: 99%
“…Climatologically last days of CDD appeared in later half of winter monsoon (see Supplement-2). Recently, Wang et al (2009) found that the East Asian winter monsoon became weaker since around the late 1980s. The weakening of the East Asian winter monsoon suggests a decrease of frequency and/or intensity of the cold surge from Siberia into the South China Sea and the Philippine Sea.…”
Section: Resultsmentioning
confidence: 99%
“…According to Wang and Chen (2010), EAWMIs can be classified into four types: (1) east-west pressure gradient indices (e.g., Wu and Wang 2002;Chan and Li 2004;Wang et al 2009b;Wang and Chen 2014), (2) low-level meridional wind indices (e.g., Ji et al 1997;Lu and Chan 1999;Yang et al 2002), (3) upper-level zonal wind shear indices (e.g., Jhun and Lee 2004;Zhu 2008;Li and Yang 2010), and (4) EA trough indices (e.g., Wang et al 2009a;Wang and He 2012). The EAWM-related circulation and air temperature anomalies are well delineated by these indices (Ji et al 1997;Jhun and Lee 2004;Chen 2010, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, as seen in Fig. 1, and as suggested by previous studies (Hu and Tung, 2002;Wang et al, 2009), the amplitudes of planetary waves in the NH stratosphere always appear to be much larger than those in the troposphere, and thus, in this study, it is inadequate to compare the absolute amplitude values between stratospheric and tropospheric planetary waves and to show their respective dominant structures. Therefore, at a given vertical level, we normalise the amplitude of each wave component (k, l) by dividing the amplitude values by the maximum value among them, and refer them to as the normalised amplitudes.…”
Section: Spatial Spectral Expansionmentioning
confidence: 56%
“…Meanwhile, the PWV is important for the northÁsouth transport of momentum, heat and mass (Chen and Huang, 2002;Randel et al, 2002), and is related to regional and hemispheric climates (Chen et al, 2005;Wang et al, 2009). Previous theoretical studies have suggested a significant influence of mid-latitude westerly flow on the propagation and evolution of planetary waves (Rossby, 1939;Yeh, 1949;Kuo, 1956;Charney and Drazin, 1961).…”
Section: Introductionmentioning
confidence: 99%